Organizational and technological aspects of applying ecological criteria in innovative low-rise construction - Perehinets, Ivan; Nazarenko, Ivan; Nesterenko, Mykola; Nesterenko, Tetiana (Academic journal Industrial Machine Building Civil Engineering, 2022)
At the current stage of society's development, more and more attention is paid to the search for constructive solutions to facilitate a healthy lifestyle. The work presents a cluster approach to the formation of the project of an innovative low-rise building under the conditions of ensuring environmental criteria, the principles of green construction by the flow method of raising buildings from ecological materials and quickly assembled modular elements. Such houses have low energy costs and make the most of the circle of quality and comfortable living. The solution of the specified approach and the adoption of relevant decisions were carried out using classical parametric system analysis and structural synthesis.
Keywords: flow construction method; energy efficiency; cluster construction; digitalization of the construction industry; low-rise construction